Zmiany poziomu spożycia żywności w Polsce - Laskowski, Wacław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The total amount of consumed food decreased in Poland. It is observed the decrease of consumption of cereals, potatoes, milk and butter. The changes are observed within the structure of food consumption as well. Beef consumption decreases, and poultry and plant fat consumption increases. In the future there are expected lower changes of consumption. There is observed the decrease of energy and nutritious value of daily food rations, what is justified. The change of nutritious value causes a lot of hazards to health. The most dangerous effect is the drastically decrease of calcium intake in the period of 20 years